Pengaruh Nilai Taksiran, Promosi, dan Ijarah Terhadap Keputusan Nasabah Pembiayaan Barang Gadai Emas (Rahn) dan Pelayanan pada Bank Syariah Mandiri - Ilham Ilham (At-Thariqah: Jurnal Ekonomi, 2021)
This research is a descriptive quantitative study. Primary data is obtained through data collection in the form of questionnaires that have been distributed to related informants. The respondents of this study were 30 customers who were going to and were already using Sharia pawning services at Bank Syariah Mandiri KC Makassar using purposive sampling technique. And analysis using SPSS.23 with multiple linear regression analysis tools. The research result obtained is the value of estimation and ijarah which has no effect on customer decisions. However, promotion of customer decisions has a positive effect on using gold pawning (Rahn) at Bank Syariah Mandiri KC Makassar.